ANALYSIS DISTRIBUTION OF MANGROVES IN THE BANTAN DISTRICT, RIAU PROVINCE USING SATELLITE IMAGE DATA LANDSAT 8 - S. Pane, Rolis; Mubarak, Mubarak; Efriyeldi, Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study aims to determine the distribution of mangroves and map the mangrove using satellite image data in the district of Bantan, Riau Province. Determination of the sampling location with purposive sampling with 3 station point, namely Jangkang Village, Selat Baru Village and Bantan Tengah Village, Bantan District. This research was carried out in April 2018 in Bantan District. Then analyzed in the Oceanographic Physics Laboratory Department of Marine Sciences, Riau University. The results of analysis of February 2018 landsat 8 image recording were 184.251 ha. The highest tree density in3 station points, namely Rhizophora apiculata, namely 500 ind/ha and the lowest tree density, Bruguiera gymnorrhizaand Xylocarpus granatum with 33.33 ind/ha. The highest seedling density wasRhizophora apiculata, wich is 2.000 ind/ha and the lowest density Bruguiera gymnorrhizawith 133.33 ind/ha. The number of mangrove species found were Rhizophora apiculata, Avicennia alba, Sonneratia ovata, Rhizophora mucronata, Xylocarpus granatum, and Bruguiera gymnorrhiza.      Keyword: image data, mangrove, Bantan District